TMJ Changes Before and After Implant of Posterior Partial Edentulous Patients Free of TMD Signs Under the Scope of Cadiax Compact II Device - Alhuseiny, Hasnaa Jameel Sharrad; Al-Aswad, Fawaz Dawood; Balsam Saadi Abdulhameed; Almayyahi, Thaer Hameed Mohsin; AL-Huseiny, Muayed S; Alhuseiny, Ahmed Sattar Sajit (South Eastern European Journal of Public Health, 2024)
Introduction: Assessing occlusion and TMJ discrepancies presents a persistent challenge for health professionals due to the complexity of the conditions that include accurate: diagnostic methods, treatment, associated comorbidities. Researches are being delved in this field. Cadiax Compact II is one of the technological innovations that can analyze and provide a simple and minimally invasive way, enabling early preventive action and treatment with a long-term impact on the good functioning of the masticatory system. Objectives: The objective of this research is to evaluate TMJ changes among dental implant patients. A comparison of the implant impact on posterior partial edentulous patient is taken place by the aid of Cadiax Compact II. Cadiax Compact II investigates in parameters such as Immediate Side-Shift (ISS), Sagittal Condylar Guidance (SCG), and Transverse Condylar Guidance (TCG) that are derived from mandible movements (opening, closing, protrusion, retrusion, and lateral excursion). The objective is to evaluate the changes in TMJ before and after implants in partial edentulous (posterior teeth) patients. Methods: Condylography using Cadiax Compatct II device (Gamma Dental, Klosterneuburg, Austria) was conducted on 40 patients. R statistical software was used to perform statistical analysis to perform a cephalometric analysis. Results: Age groups covered are (<40), (40-49), (50-59), and (≥ 60). Alpha value, level of uncertainty, was chosen to be 0.05. There is no statistical evidence in the change of ISS, SCG, and TCG before and after implant in the age groups (<40) and (40-49); however, there is a significant statistical change in age groups (50-59) and (≥ 60) with p-value <0.05. Conclusions: This research extended from December 2022 to March 2024 to cover time changes on mandible bone structure. The research outcomes revealed that implant has pronounced impact on TMJ articulation during opening, protrusion, retrusion, and lateral movements through (ISS, SCG, and TCG or so-called Bennet Angle) variables. Evidence-based statical tests with p-value < 0.05 showed that (ISS, SCG, TCG, and Bennet Angle) variables changed in age groups (50-59) and (≥ 60) from abnormal ranges to the normal ranges after implant. However, no statistical evidence was approved of the implant impact on age groups (<40) and (40-49). Though these age groups have normal ranges before and after implants.